2012
DOI: 10.4212/cjhp.v65i3.1143
|View full text |Cite
|
Sign up to set email alerts
|

A Needs Assessment Study of Hospital Pharmacy Residency Preceptors

Abstract: Background: Canadian pharmacy residency programs rely on preceptors to support the growing demand of graduates wishing to pursue hospital residencies. Understanding the educational needs of these preceptors is important to ensure that they are well prepared to deliver successful programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…While limited literature is available regarding residency program and pharmacy education perspectives, the viewpoints of institutional administrators have not been adequately explored. [7][8][9][10][11] When surveyed, RPDs and health-system personnel identified a need for more resources for preceptor development. 7 Additional teaching challenges include insufficient time, difficulty balancing precepting and workload responsibilities, inability to provide effective feedback and perform evaluations, and insufficient assistance to manage challenging learner situations.…”
Section: Introductionmentioning
confidence: 99%
“…While limited literature is available regarding residency program and pharmacy education perspectives, the viewpoints of institutional administrators have not been adequately explored. [7][8][9][10][11] When surveyed, RPDs and health-system personnel identified a need for more resources for preceptor development. 7 Additional teaching challenges include insufficient time, difficulty balancing precepting and workload responsibilities, inability to provide effective feedback and perform evaluations, and insufficient assistance to manage challenging learner situations.…”
Section: Introductionmentioning
confidence: 99%
“…Another study demonstrated that pharmacy residency preceptors expressed having learning and educational support needs in the areas of communication skills, giving effective feedback, clinical knowledge, and mentorship programs. 26 The preceptors also preferred 1-day training sessions or online learning modules every other year for ongoing educational support. As mentioned previously, Vos and Trewet 10 developed and implemented a comprehensive PDP that included live and recorded online programming, a preceptor manual, a preceptor newsletter, live events, and one-on-one practice site visits; they also collected over 5,000 evaluations of preceptor performance by students.…”
Section: The Continuing Professional Development (Cpd) For Volunteer Preceptorsmentioning
confidence: 99%
“…The second year, referred to as post graduate year 2 (PGY2), is focused on a specific area of practice state, possibly leading to pharmacy specialty certification 3. In Canada, a pharmacy residency consists of one year of structured rotations in an hospital settling5, covering various aspects such as pharmacy practice and administration, internal medicine, pediatrics, cardiology, surgery, nephrology, gastrointestinal systems, emergency medicine, intensive care, ambulatory care, and toxicology 6. In France, residency for pharmacists, termed “Internat de Pharmacie”, lasts four years and takes place in university hospitals associated with pharmacy faculties 7.…”
Section: Introductionmentioning
confidence: 99%
“… 3 In Canada, a pharmacy residency consists of one year of structured rotations in an hospital settling 5 , covering various aspects such as pharmacy practice and administration, internal medicine, pediatrics, cardiology, surgery, nephrology, gastrointestinal systems, emergency medicine, intensive care, ambulatory care, and toxicology. 6 In France, residency for pharmacists, termed “Internat de Pharmacie”, lasts four years and takes place in university hospitals associated with pharmacy faculties. 7 French pharmacy residents enroll into one of the three defined pharmacy residency specialties: “Medical Biology”, “Hospital Pharmacy” and “Pharmaceutical Innovation and Research”.…”
Section: Introductionmentioning
confidence: 99%